Nonspherical chiral helical polymer particles with programmable morphology prepared by electrospraying. Issue 48 (29th November 2019) - Li, Pengpeng; Pan, Kai; Deng, Jianping
Abstract : We anticipate that nonspherical chiral particles may open up a new research field as advanced functional micro- and nanomaterials. Abstract : Chirality and chiral materials demonstrate ever-growing importance. As a new type of chiral material, chiral polymer particles hold huge potential in both scientific research and practical applications. Meanwhile, nonspherical polymer particles (NPPs) have witnessed substantial progress in recent years because of their unique structures and especially the properties distinguishable from the corresponding spherical particles. We hypothesize that combining chirality with NPPs will open up an unprecedented category of advanced materials. The present contribution reports the first protocol for preparing electrosprayed nonspherical chiral particles constructed from chiral helical polymers, using helical substituted polyacetylenes as the model. SEM images demonstrate the successful fabrication of nonspherical chiral particles with tunable morphologies (bowl-, golf- and apple-like particles). Circular dichroism (CD) measurement proves the remarkable optical activity of the particles, which is observed in the predominantly one-handed helical polymer chains. The present work establishes a novel, versatile, and powerful platform for preparing nonspherical chiral polymer particles with controllable morphology.